Two Factors Influencing Residual Motion Estimation in Airborne SAR Images with MTPT - Zhong Xue-lian; Chen Ren-yuan; Yang Ran; Wu Tao (Leida xuebao, 2013)
motion errors, frequently occur in SAR images. For airborne SAR system with very high resolution and airborne repeat-pass SAR interferometry, the residual motion errors must be estimated and compensated. Multi-squint Technique with Point Targets (MTPT) is able to estimate the residual motion errors for an individual SAR image, but errors in the platform velocity and the slant range will deteriorate the accuracy of the method. Based on the detailed analysis of the velocity and slant range to residual motion error estimation, simulated and real SAR data are used to validate it in this paper. It is also pointed out that though MTPT is able to estimate the errors in the velocity and slant range, it is sensitive to the phase error. Therefore, it is advised that the errors in the velocity and slant range should be removed with other precise method before MTPT is utilized to estimate the residual motion errors.